CONTESTING TECHNOCOLONIALISM? THE ’ORDINARY TRANSCRIPTS’ OF EVERYDAY RESISTANCE - Madianou, Mirca (AoIR Selected Papers of Internet Research, 2023)
This paper investigates the extent to which marginalized communities contest practices of datafication and technological experimentation which are becoming increasingly ubiquitous in the aid sector. Drawing on seven years of research in the humanitarian and development sectors, the paper explores forms of resistance to digital aid practices. The paper is divided into two parts. The first section observes how datafication and digital innovation in the aid sector rework the colonial genealogies of humanitarianism and digital technology. I then theorize resistance in situations of asymmetrical power. The second section discusses empirical examples of everyday contestation. Drawing on Scott’s notion of the ‘hidden transcripts’ (1985), the paper develops the term ‘ordinary transcripts’ to illustrate the modest critique of digital power through everyday life practices such as non-participation and the oppositional appropriation of digital aid projects. Listening to the ‘ordinary transcripts’ of everyday resistance is also partly a methodological argument as it is only through ethnographic encounters that these small acts of contestation can be noticed. The paper concludes that the arguments about digital power and the persistence of colonial legacies do not preclude the acknowledgement of human agency. However, the ordinary transcripts of everyday resistance do not equal decolonization which requires a radical restructuring of power relations. Still, ordinary resistance needs to be recognized for it may contain the seeds of future decolonial struggle.